Emissions trading and productivity: Firm-level evidence from German manufacturing - Benjamin Johannes Lutz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
I study the causal effect of the European Union Emissions Trading System (EU ETS) on the productivity of German manufacturing firms. Using administrative firm-level data, I estimate robust production functions for narrowly defined industries. This approach allows for an endogenous dynamic productivity process and corrects for simultaneous changes in input use or productivity after a firm is regulated by the EU ETS. After estimating the firm specific productivity, I employ a difference-in-differences framework in order to identify and quantify the average treatment effect of the EU ETS on the productivity of regulated firms. The results suggest no significant negative effect of the EU ETS on productivity. In contrast, the EU ETS had a positive effect on productivity during the first compliance period. An alternative identification strategy based on a combination of the difference-in-differences framework and nearest neighbor matching supports this finding. A subsample analysis provides evidence that the effect of the EU ETS is heterogeneous across industries.
Keywords: D22; D24; Q52; 330; Control of Externalities; Emissions Trading; Robust Production Function Estimation; Productivity; Difference-in-Differences